Reducing the use of imprisonment. Lessons from Probation Day Centres in England and Wales: 1970–2000 - Vanstone, Maurice (Probation journal, 2023)
Day Reporting Centres as an alternative to prison have become a feature of the Criminal Justice Systems of most States in America. In contrast, Day Centres have virtually disappeared from the curricula of Probation services in England and Wales. In this paper we look back on the short history of day centre provision in this country and examine what can be learned from its different forms and assess the viability of reintroducing the concept as a means of significantly reducing the use of imprisonment this side of the Atlantic.